Dampak Pembelajaran Sirah Nabawiyah Terhadap Pembentukan Karakter Moral Siswa Di SMK Muhammadiyah 02 Boja - Robieth, Ahmad; Hadi, Syaiful (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The impact of nabawiyah sirah learning on the formation of student moral character Character education is an important aspect in the education system that aims to shape students who have noble, disciplined, and responsible students. One effective method of instilling moral values is through learning Sirah Nabawiyah, namely the study of the life of the Prophet Muhammad which is full of exemplary. This study aims to analyze the impact of Nabawiyah Sirah Learning on the formation of student moral character, identify the values that can be internalized, and evaluate the effectiveness of its application in the SMK Muhammadiyah 02 Boja. The study uses a qualitative approach with case study methods carried out in Islamic -based schools. Data was collected through observation, interviews with Islamic Religious Education Teachers (PAI). The results showed that Nabawiyah Sirah Learning contributed significantly in shaping the moral character of students, especially in terms of honesty, responsibility, discipline, and empathy attitudes and social care. These values are embedded through interactive learning methods, such as discussion, reflection, and implementation in everyday life.nnHowever, this research also found several obstacles in the application of Sirah Nabawiyah learning, such as lack of time allocation in the curriculum and the lack of parental involvement in supporting the internalization of moral values at home. Therefore, more systematic strategies are needed, such as strengthening collaboration between school and family as well as the development of learning methods that are more contextual and applicative. Thus, Nabawiyah sirah learning can be an effective instrument in shaping student moral character if implemented with the right method and optimal support from the educational environment.